2020
DOI: 10.1016/j.jgo.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, treatment patterns, prognostic determinants and outcome of peripheral T cell lymphoma and natural killer/T cell non-Hodgkin Lymphoma in older patients: The result of the nationwide multi-institutional registry Thai Lymphoma Study Group

Abstract: Introduction: Peripheral T cell NHL (PTCL) and natural killer/T cell NHL (NKTCL) are relatively rare disorders. Data on clinical presentation, treatment and outcome are limited especially in older age groups. Methods: We identified 127 patients with PTCL and NKTCL, excluding cutaneous T/NK cell lymphoma, aged over 60 years old from Thailand nationwide multicenter registry. Results: Of 127 patients, median age of diagnosis was 67 years old. Patients aged older than 75 years old had similar characteristics to yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In fact, it was reported that patients who receive low-intensity treatment performed worse than those who are treated with standard dose IV schedules. However, the "lower intensity" group received either the cyclophosphamide-vincristine-prednisolone (CVP) intravenous schedule or a single-agent chemotherapy with palliative intent [19]. We acknowledge our study on this rare disease has a small sample size, which limits the relevance of our findings and, thus, no definitive conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, it was reported that patients who receive low-intensity treatment performed worse than those who are treated with standard dose IV schedules. However, the "lower intensity" group received either the cyclophosphamide-vincristine-prednisolone (CVP) intravenous schedule or a single-agent chemotherapy with palliative intent [19]. We acknowledge our study on this rare disease has a small sample size, which limits the relevance of our findings and, thus, no definitive conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 95%
“…The authors concluded that multi-agent chemotherapy (largely CHOP) should be given whenever possible and that a comprehensive geriatric assessment is useful. 67 A Korean study in 44 patients over 70 or between 65 and 70 but with co-morbidities (median age 74) gave very similar outcome data. Patients received dose-attenuated CHOP (cyclophosphamide: 562.5 mg/m 2 , doxorubicin: 37.5 mg/m 2 , vincristine: 1.4 mg/m 2 , and prednisolone: 100 mg for five days; 25% reduced dose of cyclophosphamide and doxorubicin) as first-line therapy.…”
Section: The Treatment Of Elderly Patientsmentioning
confidence: 91%
“…The choice of chemotherapy remained significant even after adjusting for age, comorbidity, performance status and IPI. The authors concluded that multi‐agent chemotherapy (largely CHOP) should be given whenever possible and that a comprehensive geriatric assessment is useful 67 . A Korean study in 44 patients over 70 or between 65 and 70 but with co‐morbidities (median age 74) gave very similar outcome data.…”
Section: The Treatment Of Elderly Patientsmentioning
confidence: 97%